2003
DOI: 10.1021/es0264596
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates, Alkylphenols, Pesticides, Polybrominated Diphenyl Ethers, and Other Endocrine-Disrupting Compounds in Indoor Air and Dust

Abstract: Chemicals identified as endocrine-disrupting compounds (EDCs) have widespread consumer uses, yet little is known about indoor exposure. We sampled indoor air and dust in 120 homes, analyzing for 89 organic chemicals identified as EDCs. Fifty-two compounds were detected in air and 66 were detected in dust. These are the first reported measures in residential environments for over 30 of the compounds, including several detected at the highest concentrations. The number of compounds detected per home ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
619
19
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 922 publications
(715 citation statements)
references
References 27 publications
37
619
19
4
Order By: Relevance
“…Bolinas is a rural community north of San Francisco. Sampling protocols and analytical methods have been described in detail elsewhere (4). Briefly, dust samples were collected using a Eureka Mighty-Mite vacuum cleaner attached to a Teflon crevice tool, modified to collect dust into a cellulose thimble (Whatman Inc., Clifton, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Bolinas is a rural community north of San Francisco. Sampling protocols and analytical methods have been described in detail elsewhere (4). Briefly, dust samples were collected using a Eureka Mighty-Mite vacuum cleaner attached to a Teflon crevice tool, modified to collect dust into a cellulose thimble (Whatman Inc., Clifton, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Inhalation exposure to toner dust has been implicated in case reports as causing respiratory impairment (Gallardo et al 1994;Armbruster et al 1996 Carlsson et al, 2000). PBDEs, which are classified as endocrine-disrupting compounds (Rudel et al 2003), have been shown to accumulate in human breast milk (Noren and Meironyte 2000). Recent evidence suggests that increased contact with office equipment leads to higher doses and tissue levels of these pollutants.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Although MXC is less environmentally persistent than the related organochlorine pesticide, DDT (1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane), residues of MXC have been reported in soils, tissues of wildlife, and in household dust (Campoy et al, 2001;Rudel et al, 2003;Vorkamp et al, 2004;Wan et al, 2005). MXC metabolism by P450 isoforms both in vitro and in vivo have led to the identification of two major metabolites, formed by its sequential demethylation: the chiral mono-demethylated 2-(p-hydroxyphenyl)-2-(p-methoxyphenyl)-1,1,1-trichloroethane (OH-MXC) and the bis-demethylated 2,2-bis(p-hydroxyphenyl)-1,1,1-trichloroethane (HPTE) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%